Environmental Stress Induces Trinucleotide Repeat Mutagenesis in Human Cells by Alt-Nonhomologous End Joining Repair. Issue 15 (31st July 2016) - Chatterjee, Nimrat; Lin, Yunfu; Yotnda, Patricia; Wilson, John H.
Abstract: Multiple pathways modulate the dynamic mutability of trinucleotide repeats (TNRs), which are implicated in neurodegenerative disease and evolution. Recently, we reported that environmental stresses induce TNR mutagenesis via stress responses and rereplication, with more than 50% of mutants carrying deletions or insertions—molecular signatures of DNA double-strand break repair. We now show that knockdown of alt-nonhomologous end joining (alt-NHEJ) components—XRCC1, LIG3, and PARP1—suppresses stress-induced TNR mutagenesis, in contrast to the components of homologous recombination and NHEJ, which have no effect. Thus, alt-NHEJ, which contributes to genetic mutability in cancer cells, also plays a novel role in environmental stress-induced TNR mutagenesis. Graphical Abstract: Highlights: Environmental stresses induce TNR mutagenesis by rereplication in human cells. siRNA knockdown was used to define repair pathways for the assumed double-strand break intermediate. Knockdown of Rad51 and BRCA1 had no effect, ruling out homologous recombination. XRCC4 and LIG4 knockdown had no effect, excluding classic nonhomologous end joining. PARP1, XRCC1, and LIG3 knockdowns link alt-NHEJ to stress-induced TNR mutagenesis.